Vulnerabilidade a transmissão vertical da sífilis: situações programáticas da atenção primária a saúde vivenciadas por gestante no pré-natal - Araújo Junior, David Gomes (2019)
The study aims to describe the situations of programmatic vulnerability investigated, in the context of the congenital syphilis theme in the city of Sobral - CE, providing the opportunity for updated knowledge, which may support the implementation of strategic and political actions. This is a case study, descriptive, analytical and qualitative approach. An analytical matrix of the situations of programmatic vulnerability of PHC health services to Congenital Syphilis was developed and applied based on Florêncio (2018). The research field consisted of Primary Health Care (PHC) of the municipality Sobral - Ceará. The study participants will correspond to mothers who have children diagnosed with congenital syphilis in 2017, primary health care professionals who accompanied them during prenatal care in this case were chosen by the nurse and managers. For the development of this research the perception of different sources of information was used. Thus, for data collection will be conducted semi-structured interviews with the help of guiding questions with women / mothers, nurse managers. Data appreciation was made through the Content Analysis Technique proposed by Bardin. The study respected the ethical principles according to CNS Resolution 466/2012 and received a favorable opinion from the Research Ethics Committee of Vale do Acaraú State University, under Opinion number: 3.377.307. From the organization of empirical data, it was possible to analyze the discourses of women and professionals in two major thematic classes that are subdivided into four categories containing 17 other subcategories, which show different situations of programmatic vulnerability. In the thematic class Structural Situations of Vertical Transmission Vulnerability of Syphilis was classified into two categories: HUMAN RESOURCES AND MATERIALS (Limitation on availability of educational material and prevention; Limitation on availability of treatment / medication; Limitation on availability of examinations and Limited Human Resources) and TECHNICAL-SCIENTIFIC PROCESS OF PROFESSIONALS (Absence of professional training; Fragility in academic / vocational training; Fragility in professional knowledge). In the second thematic class Situations of vulnerability of the work process to the vertical transmission of Syphilis was evidenced in two other categories: CARE PRACTICES (Lack of information to the patient about the procedure, examination and disease; Fragility in the examination and treatment records; diagnosis, treatment and follow-up; Fragility in partner care and treatment; Impaired Bond and Prenatal Fragility) and SERVICE MANAGEMENT AND ORGANIZATION (Notification and surveillance system weakness; Poor communication between health services; Impaired accessibility; Limitation of actions or programs of health education and Fragility at the time of completion and results of examinations). Although there are measures to prevent CS, there are a number of factors that hinder its eradication and increase the vulnerability of women to have a child with CS in Brazil. Factors that are not only related to the lifestyle of pregnant women with syphilis and their partner, but include socio-political and cultural aspects, as well as accessibility to organized actions and health promotion, protection and recovery services of these individuals.